Implementation of Outseal PLC for Monitoring kWh Meters in the Commercial Sector Using Android-Based HMI - Ardiansyah, Ardiansyah; Sukardi, Sukardi; Hambali, Hambali; Mukhaiyar, Riki (Jurnal Teknik Elektro Indonesia, 2024)
The increasing demand for electricity in the commercial sector necessitated the development of an efficient monitoring system to manage energy consumption. This study aimed to design and implement a monitoring sistem for kWh meters using an Outseal PLC integrated with an Android-based HMI. The system utilized the Outseal PLC as the primary controller, interfacing wirelessly with a Modbus HMI through a DT-06 Wi-Fi Module. A PZEM-004T sensor was used to measure voltage, current, power, and energy consumption. The PLC communicated with the sensor via Modbus protocol using a Max485 module. The data collected was displayed on the HMI, allowing real-time monitoring of power usage. Experimental methods involving the design and testing of both hardware and software components were employed. Results demonstrated that the system accurately measured electrical parameters with minimal error. The voltage and current readings showed average errors of 0,08% and 0,23% respectively for an 85 Ω load, 0,92% and 2,81% for a 14 Ω load. Power measurements had an average error of 0,15% for an 85 Ω load and 1,68% for a 14 Ω load. The Wi-Fi connection range was tested and found to be effective up to 14 meters without obstacles. This study concluded that the Outseal PLC-based monitoring system is a reliable and cost effective solution for managing energy consumption in the commercial sector.